Penerapan Desain Interaksi Pada Perancangan Kalkulator Sederhana Untuk Tunanetra - Agif Sasmito; Hurriyatul Fitriyah; Mochammad Hannats Hanafi Ichsan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Nowadays, in the current technological development, in education and work required mobility such as calculating. Mathematics is a systematic numerical used the calculation basic. The basic concepts of mathematics are filled with aspects visually. Calculator used as a calculations. The calculator available in the markets with smooth input keys and LCD outputs are useless for them. An optimal solution for them is braille calculator 4x4 membrane keypad with audio output. In this research, Implementation has simplified the existing braille calculator. The Design using 6 point of braille system with 3x2 button combination and backspace feature. User could input numbering from 0 to 9. The process are what is wanted, analysis, design, prototype and implementation/deploy. Implementation of system using 6 buttons is packed in a 7,5cm x 7,3cm x 5cm box. Keypad each other in a 0,6 cm. The distance used button each other to decrease input error. The result of standard testing with 2 visually impaired. This testing showed 100% rate. And average score of likert scale (1-5) has scored 5. So this calculator is very deserving to be used as calculating tool for the blinds.